Status and problematic issues of joint replacement in Ukraine (an enforcement of the XVI Congress of orthopaedics and traumatologists of Ukraine) - Korzh, Mykola; Gaiko, Georgy; Filipenko, Volodymyr; Gerasimenko, Sergey; Tankut, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Status of development and outlooks of joint replacement procedures in Ukraine were analyzed. It is noted that under the auspices of the Ministry of Health, the National Academy of Medical Sciences, and the Association of Orthopaedic Surgeons and Traumatologists of Ukraine there were established and actively deal some regional centers in Kiev, Kharkov, Dnepropetrovsk, Donetsk as well as regional and city centers equipped with modern kinds of endoprostheses and instruments. There are qualified surgeons experienced on joint replacement, anesthesiologists and rehabilitation specialists working there. Over the past 5 years the specialists of these centers for improvement of their skills have been trained in leading hospitals in Ukraine, Europe and America. Many of anesthesiologists, rehabilitation specialists as well as nurse practitioners and other medical staff also were trained, and this significantly improved the quality of joint replacement procedures as a whole, and social adaptation of the patients. Ongoing researches on the development of novel domestic endoprostheses keep doing. At the Sytenko Institute for Spine and Joints Pathology of the National Academy of Medical Sciences of Ukraine along with the SPA "Monocrystal" and the LLC "Sumaral-Med" a novel construct of hip endoprosthesis with friction pair of monocrystalline corundum (sapphire) was developed and passed clinical testing. In Kiev at the Institute for Orthopeadics and Traumatology of the National Academy of Medical Sciences of Ukraine construct of total revision hip cementless endoprosthesis with modern titanium covering, perfect anatomical shape and wear resistant pair of friction with ceramic head was designed. Despite on a special computer program called "Register" established in Ukraine which allows you to enter information about the operations of replacement without too much difficulties an issue on registration and analysis of outcomes of surgeries performed remains open and unresolved. Further strengthening of the material-technical base of the centers for joint replacement procedures and for the departments of orthopedic and trauma in the regional hospitals is important for solving this problem. An issue on annually increasing amount of revision joint replacement surgeries remains complicated and unresolved. For instance, in the Western Europe the number of revision cases is about 20%. Analysis of this situation made at the Sytenko Institute for Spine and Joints Pathology indicates that the number of revision cases in Ukraine does not exceed 10%. This is a worrying signal for the future. Fitting up with revision systems, instruments and properly trained professionals presents an acute problem. Rehabilitation centers for patients with endoprostheses of the large joints existing in Ukraine have not yet fully ensure process of treatment which also requires solutions. It was proposed to create the state research program "Revision hip and knee joints replacement in Ukraine" within which provision of the existing centers with necessary medical equipment, instruments and metal artificial joints will be substantiated, and development and manufacturing of surgical instruments for systems in revision cases based on domestic producers will be planned. All of this will allow improving the quality of life of the patients.